Kepemimpinan Nabi Muhammad Shalallahu ‘alahi wasallam dalam sistem pendidikan - Alkattani, Abdul Hayyie; Ramdanu, Aulia (Tawazun: Jurnal Pendidikan Islam, 2023)
The leadership of the Prophet is full of lessons full of wisdom that is certainly suitable in all conditions. Leadership is something that is often discussed in the world of education in general. With strong leadership will be able to determine success in the organization. This paper aims to explain educational leadership according to Muhammad Syafi'i Antonio. The research method used is a qualitative research method with the type of library research (library study). The primary data source is the book Muhammad Saw super leader super manager by Muhammad Syafii Antonio. The secondary data sources include books containing the journey of the Prophet Muhammad Shalallahu 'alahi wasallam among the books of Sirah Nabawiyah by Shaykh Syafiyurrahman Al-Mubarakfurry, in addition to articles related to the research theme. Leadership is an effort to be able to manage a group of people, provide encouragement and enthusiasm, supervise and evaluate in an effort to achieve the goals that have been set together. One of the success factors in education at the time of the Prophet Muhammad was the Prophet as an example and role model for his people. Prophet Muhammad SAW is likened to the living Qur'an. The attitude and character of the Prophet Muhammad is a reflection of the Qur'an. Prophet Muhammad SAW who made himself a living model which means that all the content in the Qur'an and As-Sunnah is contained in the Prophet. This makes it easier for his friends to imitate and imitate. Among educational institutions, namely (1) Dar Al-Arqam (2) Mosque (3) Ash-Shuffah (4) Kuttab. So that the existence of this institution gives the color of Islamic da'wah at the time of the Prophet SAW Abstrak Kepemimpinan Rasulullah yang sarat dengan pelajaran penuh dengan hikmah yang sudah pastinya cocok dalam segala kondisi. Kepemimpinan menjadi sesuatu yang sering menjadi pembicaraan dalam dunia pendidikan pada umumnya. Dengan kepemimpinan yang tangguh akan dapat menentukan keberhasilan dalam berorganisasi.. Dalam tulisan ini memiliki tujuan menjelaskan kepemimpinan pendidikan menurut Muhammad Syafi’i Antonio. Metode Penelitian yang digunakan adalah metode penelitian kualitatif dengan jenis library research (Studi pustaka).Sumber data Primer adalah buku Muhammad Saw Super Leader Super Manager karya Muhammad Syafii Antonio. Adapun sumber data sekunder antara lain buku-buku yang memuat perjalanan Nabi Muhammad Shalallahu ‘alahi wasallam di antara buku sirah nabawiyah karya Syaikh Syafiyurrahman Al-Mubarakfurry, selain itu artikel yang memiliki kaitan dengan tema penelitian. kepemimpinan adalah suatu usaha untuk dapat mengatur sekumpulan orang, memberikan dorongan dan semangat, melakukan pengawasan dan mengevaluasi dalam usaha untuk mencapai tujuan yang telah ditetapkan bersama. Salah satu faktor keberhasilan pendidikan zaman Nabi Muhammad Saw yaitu Rasulullah sebagai model contoh dan teladan untuk umatnya. Nabi Muhammad Saw diumpamakan sebagai Alquran yang hidup. Sikap dan akhlak Nabi Muhammmad Saw adalah cerminan dari Alquran. Nabi Muhammad Saw yang menjadikan dirinya sebagai living model yang bermakna semua kandungan dalam Alquran dan As-Sunnah terdapat dalam diri Nabi. Hal itu memudahkan para sahabatnya untuk meniru dan mencontoh. Di antara lembaga pendidikan yaitu (1) Dar Al-Arqam (2) Masjid (3) Ash-Shuffah (4) Kuttab. Sehingga dengan keeksistensian lembaga tersebut memberikan warna dakwah Islam pada zaman Nabi Saw.